2019
DOI: 10.1111/1477-9552.12359
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Commercialisation and Nutrition in Smallholder Farm Households

Abstract: Commercialisation of smallholder agriculture is important for rural economic growth. While previous studies have analysed effects of commercialisation on productivity and income, implications for farm household nutrition have received much less attention. We evaluate the effects of commercialisation on household food security and dietary quality with a special focus on calorie and micronutrient consumption. We also examine transmission channels by looking at the role of income, gender, and possible substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 37 publications
4
89
0
Order By: Relevance
“…T i in Equation 6 is also potentially endogenous and this may arise because of unobserved heterogeneity, reverse causality, or measurement error, leading to biased estimates (Ogutu et al., 2019; Ogutu & Qaim, 2019). That is, the treatment variable T i may be correlated with the error terms in Equations 4 and 5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…T i in Equation 6 is also potentially endogenous and this may arise because of unobserved heterogeneity, reverse causality, or measurement error, leading to biased estimates (Ogutu et al., 2019; Ogutu & Qaim, 2019). That is, the treatment variable T i may be correlated with the error terms in Equations 4 and 5.…”
Section: Methodsmentioning
confidence: 99%
“…Ogutu et al. (2019) for instance examined the impact of agricultural commercialization (including crops and livestock), on income and poverty in Kenya. They found that commercialization increased income by 17% and reduced the prevalence of poverty by 5.1 percentage points.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remoteness can undermine the efforts made to improve food security, feeding practices and diets by limiting access to quality food markets [41,42]. The contribution of market access in improving smallholder farmers' nutrition is documented in literature [43][44][45][46][47][48][49][50]. However, empirical evidence on the nexus between accessibility to food market, caregivers' knowledge of appropriate diet for preschool children, and dietary diversity in Nigeria is scanty.…”
Section: Introductionmentioning
confidence: 99%
“…This makes the treatment endogenous and addressing the endogeneity of the treatment variable needs the identification of an instrument variable. A suitable instrument must not have any relationship with the outcome variables/dependent variables (exclusion criterion), but must be significantly related to the endogenous variable (relevance criterion) [41,42]. The instrument identified in this study is in contact with agricultural extension agents.…”
Section: Econometric Frameworkmentioning
confidence: 99%